Análisis de un modelo de gestión organizacional para la nacionalidad kichwa de la región amazónica, representada por la CONFENIAE, para su desarrollo social y económico en el periodo 2013 al 2018 - Shiguango Grefa, María Mélida (2015)
Designing Organizational Management Model allows Kichwa´s leaders and organizations to improve their services with quality and warmth, requires the direct participation of the sectional governments for in reality the proposal be captured, within the Constitution of the Ecuadorian State recognizes the duties of communities, villages and nationalities "Building and maintaining organizations representing, in the framework of respect for pluralism and the cultural, political and organizational diversity. The State recognized and promoted all forms of expression and organization, "and the Organic Code of Territorial Ordering Autonomy and Decentralization-COOTAD guarantees "Territorial Constituencies of Municipalities, Communities, village and indigenous nationalities, Afroecuadorians and Montubios ". It is a very important tool for nationality as it defines the organizational, political and administrative life, the participation of the actors and involvement of regional partners should be the primordial to decision making.